Scrutinize Analysis of Crime Investigation – Assigned Weighted Approach - Kittappa, Thiagarajan; Snehal, S. Mrithul; Amrutha, J.; Osborne, John; Nishanth, A.; Anburaja, Anish (Migration Letters, 2023)
This study focuses on trust rating between police records and observed current case’s data, employing a weighted graph approach to make informed decisions in different criminal investigations. Four distinct cases, ranging from theft to homicide, were examined, each with its own assigned trust levels. The outcomes of these cases varied, with trust ratings playing a significant role in influencing the final decisions made by law enforcement agencies. The results underscore the importance of considering specific evidence and circumstances in the determination of suspects guilt or innocence in AI based outputs